Molecular simulation and mathematical modelling of glass transition temperature depression induced by CO2 plasticization in Polysulfone membranes - Lock, S.S.M. (Institute of Physics Publishing, 2017)
A sequence of molecular modelling procedure has been proposed to simulate experimentally validated membrane structure characterizing the effect of CO2 plasticization, whereby it can be subsequently employed to elucidate the depression in glass transition temperature (Tg ). Based on the above motivation, unswollen and swollen Polysulfone membrane structures with different CO2 loadings have been constructed, whereby the accuracy has been validated through good compliance with experimentally measured physical properties. It is found that the presence of CO2 constitutes to enhancement in polymeric chain relaxation, which consequently promotes the enlargement of molecular spacing and causes dilation in the membrane matrix. A series of glass transition temperature treatment has been conducted on the verified molecular structure to elucidate the effect of CO2 loadings to the depression in Tg induced by plasticization. Subsequently, a modified Michealis-Menten (M-M) function has been implemented to quantify the effect of CO2 loading attributed to plasticization towards Tg . © Published under licence by IOP Publishing Ltd.